Bureaucratic Dynamics and Their Impact on the Local Business Environment: Local Government Strategies in Promoting Economic Growth - Andi Masrich; Irwandi Irwandi; Tituk Utari; Masnilam Hasibuan; Radi Sahara (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
In the context of globalization and rapid economic change, the role of local governments in managing bureaucratic dynamics and developing strategies to encourage local economic growth has become increasingly crucial. Local businesses are the backbone of a region's economy, and the performance of local government bureaucracy and policies can have a significant impact on community welfare and potential economic growth. This research aims to analyze bureaucratic dynamics in the local business environment and local government strategies for encouraging economic growth. This research uses a qualitative descriptive method, which makes it possible to analyze bureaucratic dynamics and regional government strategies comprehensively. Research data was obtained through a literature review of research results and previous studies that are relevant to this research topic. The research results reveal that strong political support, availability of adequate resources, and cooperation between government institutions are essential supporting factors for local government strategies in encouraging local economic growth. On the other hand, obstacles such as conflicting policies, budget constraints, and economic uncertainty are challenges that need to be overcome. These conclusions provide an in-depth understanding of the complexity of the role of local government in creating a business environment that supports local economic growth and provides valuable insights for public policy and decision-making at the local government level.